Bardelys the Magnificent Based on a Novel by Rafael Sabatini - Coppola, Antonio (Flicker Alley, 2009)
"Bardelys the Magnificent" (1926) is based upon the novel by Rafael Sabatini and directed by King Vidor, who just one year before had directed Gilbert in the smash hit "The Big Parade". In France "in an age of light loves and lively scandals," the Marquis de Bardelys (Gilbert), casual womanizer and accomplished swashbuckler, is entranced by Roxalanne de Lavedan (Eleanor Boardman); and against a background of knavery and intrigue, he sets out to woo and win her. Lavishly mounted and superbly directed with spectacular action scenes, Bardelys is a hugely entertaining action romance given an A-plus MGM production. The sole surviving print was found in France in 2006; the English titles are restored according to the original script. A gap in the recovered footage is bridged with stills, titles, and footage from the original trailer so the story is complete. The Mont Alto Motion Picture Orchestra provides a lovely score of period photoplay music; Antonio Coppola provides an alternate musical score on piano. This release is possible through the graciousness of Warner Bros. and Sony Pictures. [www.flickeralley.com]